Communication Error Management in Law Enforcement Interactions: A Sender’s Perspective - Oostinga, Miriam S. D. (Criminal justice and behavior, 2020)
We examined the psychological and behavioral consequences of making a communication error in expressive crisis negotiations and instrumental suspect interviews. During crisis negotiation (n = 133) or suspect interview (n = 68) training, Dutch police and probation officers received preparation material that led them to make a factual, judgment, or no error. Across both studies, errors increased officers’ negative affect, with errors leading to more stress in crisis negotiations and more distraction in suspect interviews. When comparing factual with judgment errors, factual errors led to more distraction in crisis negotiations and more negative affect in suspect interviews. Analysis of the transcribed dialogues identified four categories of response: apologize, exploration, deflect, and no alignment. Of these, negotiators used all four regularly, whereas interviewers predominantly used exploration and deflect. Our findings revealed the potentially negative effects of errors on officers and offered insights into how they could best focus to induce an appropriate response.